Improving the maturation of human pluripotent stem cell - derived hepatocyte-like cells using an automated-design of experiments approach - Fotopoulos, Lazaros (2019)
Human primary hepatocytes (pHEPs) are used as the gold standard model for drug screening and toxicity testing in the drug development pipeline. However, the rapid post isolation changes in cell structure, morphology, gene expression and metabolic activity, together with donor availability and heterogeneity, limit their utility. Directed differentiation of human embryonic stem cells (hESCs) or human induced pluripotent stem cells (hiPSCs) into hepatocyte-like cells (HLCs) can be achieved within a short time and in unlimited quantities; however their metabolic activity closely represents foetal hepatocytes but not an adult hepatocyte metabolic profile. Studies have identified compounds that can increase expression of some adult enzymes, but a systematic evaluation of multiple compounds in a range of concentrations has never been reported in human cells. Studying the maturation of HLCs requires identification of distinct markers that are only expressed in the adult liver cells to clearly evaluate maturation characteristics as the current literature predominantly investigates the expression of the characteristics observed during the foetal stages.